2005
DOI: 10.1158/0008-5472.can-04-3429
|View full text |Cite
|
Sign up to set email alerts
|

Meat, Meat Cooking Methods and Preservation, and Risk for Colorectal Adenoma

Abstract: Cooking meat at high temperatures produces heterocyclic amines (HCAs) and polycyclic aromatic hydrocarbons (PAHs). Processed meats contain N-nitroso compounds. Meat intake may increase cancer risk as HCAs, PAHs, and N-nitroso compounds are carcinogenic in animal models. We investigated meat, processed meat, HCAs, and the PAH benzo(a)pyrene and the risk of colorectal adenoma in 3,696 left-sided (descending and sigmoid colon and rectum) adenoma cases and 34,817 endoscopy-negative controls. Dietary intake was ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
164
2
2

Year Published

2006
2006
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 191 publications
(181 citation statements)
references
References 23 publications
13
164
2
2
Order By: Relevance
“…Compared with Western populations, our study population has a much lower level of meat consumption. On average, the total meat intake is only about half to one-third of that consumed in Western countries (Sinha et al, 2005;Gonzalez et al, 2006). Our findings provide potent evidence of the unfavourable role of meat intake in the development of endometrial cancer, even at a low average level of consumption, and thus strongly support public health messages suggesting that women should be encouraged to lower their meat intake.…”
Section: Discussionsupporting
confidence: 57%
See 2 more Smart Citations
“…Compared with Western populations, our study population has a much lower level of meat consumption. On average, the total meat intake is only about half to one-third of that consumed in Western countries (Sinha et al, 2005;Gonzalez et al, 2006). Our findings provide potent evidence of the unfavourable role of meat intake in the development of endometrial cancer, even at a low average level of consumption, and thus strongly support public health messages suggesting that women should be encouraged to lower their meat intake.…”
Section: Discussionsupporting
confidence: 57%
“…It has been reported that deep-frying also generates fumes containing mutagenic compounds (de Meester and Gerber, 1995;Shields et al, 1995). These mutagens or carcinogens have been linked to an increased risk of cancers among Western populations (Zimmerli et al, 2001;Sinha et al, 2005). However, in our study, we found no association between cooking patterns or doneness levels and the risk of endometrial cancer, nor did they modify the risk associated with meat intake with the exception of the positive association with deep-fried cooking observed among women whose consumption of fish was in the lowest quartile.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Die positive Assoziation wird am ehesten durch die Verarbeitung und die Zubereitungsart verursacht, wie Daten des Prostate, Lung, Colorectal, and Ovarian cancer trials zeigen. Die regelmäßi-ge Aufnahme von insbesondere durchgegartem rotem Fleisch, Speck (Bacon) und Würstchen korrelierte mit einer signifikanten Erhöhung des Risikos zur Ausbildung eines KRK [47].…”
Section: Level Of Evidence 2aunclassified
“…As will be discussed below, the generation of Maillard reaction products contributes to reducing protein digestibility. Moreover, as precursors to mutagenic heterocyclic amines, Maillard reaction products have been associated with numerous physiological problems, including pancreatic (Anderson et al, 2002), colorectal (Murtaugh et al, 2004;Sinha et al, 2005) and endometrial (Xu et al, 2006) cancers. Why we should be attracted to specific flavors at all remains unknown, but it is particularly surprising that we should demonstrate a distinct preference for flavors associated with apparently detrimental compounds.…”
Section: Increased Food Intakementioning
confidence: 99%